Comparative Analysis of Histopathological Alterations and Immunohistochemistry in Cattle for Diagnosis of Rabies - Beigh , Akeel Bashir; Sandhu, Bhupinder Singh; Singh , Charan Kamal; Bansal , Karan; Nilakanth , Madhav Mugale; Sood, Naresh Kumar (Brazilian Journal of Veterinary Pathology, 2013)
Comparative analysis of histopathological alterations and immunohistochemistry was performed on 15 brain samples of cow. In the present study, brain tissues were positive in 9 cases (60.0%), using polyclonal antiserum by immunohistochemistry and 7 cases (46.60%) were found positive for rabies by demonstration of Negri bodies. Hundred neurons per case were observed for Negri bodies; number of Negri bodies in positive neurons was counted and a comparison of IHC and histopathology was done. Number of neurons positive for rabies virus antigen per 100 neurons (900 neurons) by IHC were more (665) than H& E staining (344) and average number of Negri bodies per neuron detected by IHC were more (2.97) than histopathology (1.52), therefore, IHC was found to be more sensitive than histopathology.